(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
In present study, a series of chalconesemicarbazones was synthesized and evaluated for antioxidant activity by DPPH free radical scavenging assay. Most of the compounds were found to be potent antioxidant. Free radicals play an important role in various pathological and xenotoxic effects so antioxidant may have protective role in these pathological conditions. Based on the results of an anti-oxidant study, Compound 23 was the most active compound. The highest scavenger activity observed in compound 23 is probably due to the presence of hydroxyl group in the acetophenic moiety and methoxy group in aldehydic moiety of chalcone. It was found that methoxy and hydroxyl substituted chalconesemicarbazones were potent nitric oxide scavenger and unsubstituted compound showed very less activity.